Treatment of Patella fracture with tension band wiring modified technique as a gold standard option & experienced at Tertiary care hospital - Muhammad Azeem Akhuandl, Kishore kumak, Zameer Tunio’, Allah Nawaz Abbasi , Faraz Jokhio” Muhammad Ali Jamali6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
OBJECTIVE: To evaluate functional outcome of Tension Band Wiring modified Technique for treatment of patella fracture. STUDY DESIGN: Case series and observational. SETTING: This research was done at orthopedic department at PMCH NAWABSHAH SBA, from January 2017 to July 2019.METHODOLOGY: This Case Series study consisted of 15 patients treated with Modified tension band wiring technique The outcome of this procedure was assessed by Guar criteria for knee function. RESULT: Total 15 patients were evaluated in this study. The mean age was 41+5 23 is mean age, male were 73.39a. Commonly right side is more affected in this study (66.6' o) in road traffic accident by direct forces. By using guar criteria 609c was excellent, 209a are good, 13.39c shows fair result and remaining was poor 6.69a. Union time was 6 to 9 weeks in 86.69c cases. Functional outcome was excellent in 60' o patient good was seen in 20 to patients, fair in 13.339c patients & poor was in 6.69c. CONCLUSION:-Tension Band Wiring modified Techniques a Gold Standard for the patella fracture Treatment